The osteological development of nine species of Nototheniidae (Perciformes: Notothenioidei) ... - Voskoboinikova, Olga S.; Kellermann, A. (Société Française d'Ichtyologie, 1997)
The osteological development of nine species of nototheniids was investigated. All the species in general are characterized by the similar sequence of appearance of bones, except for Pleuragramma antarcticum. It is shown that the latest appearing bones are as a rule reduced in more derived species of the nototheniids and/or in advanced families of the notothenioids. The morphogenesis of certain characters of systematic value in general confirms validity of the subfamilies Nototheniinae, Trematominae and Pleuragramminae. Main trends of the skeletal development in the Nototheniidae subfamilies are considered. ...